Analisis Sarana Pencetakan Kartu Berobat Pasien Secara Berulang-Ulang Oleh Pegawai Rekam Medik Di Bagian Pendaftaran Di Rsud Teluk Kuantan Tahun 2023: Analysis of the Repeated Printing of Patient Medical Cards by Medical Record Staff in the Registration Section at Teluk Kuantan Regional General Hospital in 2023 - RICKY WIRANATA (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2024)
To enhance the quality of services within the Medical Record Installation, it is necessary to implement a patient registration system that is simple, efficient, and easily accessible. One of the essential components of this system is the patient medical card, which is issued by the medical record unit to facilitate the identification and management of patient data. The main objective of this program is to optimize the hospital’s information management system, particularly within the Medical Record Installation of RSUD Teluk Kuantan, to support accurate, timely, and integrated health data management. The activity was carried out through three main stages: Preparation Phase – including the introduction and orientation at RSUD Teluk Kuantan. Implementation Phase – involving interviews, direct observations, and document reviews within selected medical record units. Reporting Phase – consisting of the preparation of the final report (Chapters I–VIII), followed by consultations with the field supervisor and academic advisor, and concluded with a residency result seminar. The priority problem was identified using the USG (Urgency, Seriousness, and Growth) method, which determined that the main issue was the Patient Medical Card Management System at RSUD Teluk Kuantan. As part of the Action Plan, the proposed solution involved establishing a Memorandum of Understanding (MoU) between the Head of the Medical Record Installation and the Hospital Director, concerning the development and implementation of an improved patient medical card system at RSUD Teluk Kuantan. Additionally, another strategic solution was to recruit new human resources who meet the professional qualifications required for the medical record department. This step aims to strengthen the unit’s operational capacity and ensure that medical record services are conducted effectively and in accordance with hospital standards.